Uji In Vitro Asap Cair terhadap Ralstonia syzygii subsp. celebesensis Penyebab Penyakit Darah pada Pisang - Aisyah Imas; Giyanto Giyanto; Meity Suradji Sinaga; Abdjad Asih Nawangsih; Gustan Pari (Jurnal Fitopatologi Indonesia, 2018)
In Vitro Test of Liquid Smoke against Ralstonia syzygii subsp. Celebesensis, the Cause of Blood Disease in Bananas Blood disease, caused by Ralstonia syzygii subsp. celebesensis, is an important disease of banana plants in Indonesia. Several control methods have been done, but the result were not effective.  Liquid smoke from wood waste is reported to be antimicrobial, but its use for controlling R. syzygii subsp. celebesensis has never been reported. Research was conducted to examine the ability of liquid smoke produced from coconut shell (CS-LS), pinecone (P-LS), and oil palm branch (OPB-LS) in inhibiting the growth of R. syzygii subsp. celebensensis in vitro and its effect on bacterial cell morphology. Efficacy test of liquid smoke was carried out by agar diffusion method and measurement of bacterial density by spectrophotometry with ʎ 600 nm. Observation of bacterial cell morphology was carried out by electron microscopy. The CS-LS, P-LS, and OPB-LS starting from 0.5% concentration showed inhibitory activity against R. syzygii subsp. celebesensis both on triphenyl tetrazolium chloride medium and luria bertani broth. Liquid smoke also caused damage to cell walls and cell membranes. Therefore, liquid smoke has the potential to be used as component in control method for R. syzygii subsp. celebesensis.